2017
DOI: 10.1007/s11999-017-5260-6
|View full text |Cite
|
Sign up to set email alerts
|

Exchangeable Femoral Neck (Dual-Modular) THA Prostheses Have Poorer Survivorship Than Other Designs: A Nationwide Cohort of 324,108 Patients

Abstract: BackgroundExchangeable neck stems, defined as those with a dual taper (that is, a modular junction between the femoral head and the femoral neck and an additional junction between the neck and the stem body), were introduced in THA to improve restoration of joint biomechanics (restoring anteversion, offset, and limb length) and reduce the risk of dislocation. However exchangeable necks have been reported to result in adverse effects such as stem fractures and acute local tissue reaction. Whether they result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 50 publications
0
39
1
Order By: Relevance
“…The cumulative incidence of revision at 10 years in the present series was 5%, which is better than the 6-year revision incidence reported in a recent nationwide study (7,680 uncemented modular neck stems) from France (7%) (22). It is worth noting that our 10-year revision incidence is closer to that reported by the Australian Orthopaedic Association (AOA) for fixed neck stems (4.9%) than that reported for modular neck stems (9.3%) (23).…”
Section: Discussioncontrasting
confidence: 68%
“…The cumulative incidence of revision at 10 years in the present series was 5%, which is better than the 6-year revision incidence reported in a recent nationwide study (7,680 uncemented modular neck stems) from France (7%) (22). It is worth noting that our 10-year revision incidence is closer to that reported by the Australian Orthopaedic Association (AOA) for fixed neck stems (4.9%) than that reported for modular neck stems (9.3%) (23).…”
Section: Discussioncontrasting
confidence: 68%
“…Modular femoral neck designs were found to have higher revision rates compared with fixed-neck design in a recent French study of 324,108 patients. 42 A study based on the National Joint Registry for England, Wales, Northern Ireland, and the Isle of Man found that newer ceramic head designs for ceramic-on-ceramic total hip arthroplasty have lower rates of Fig. 15 Postoperative femoral neuropathy.…”
Section: Neoplasmmentioning
confidence: 99%
“…In a French study investigating 324,108 patients followed for up to 6 years from the index procedure, the cumulative revision rate was 6.5% for a modular femoral neck design compared with 4.7% for a fixed-neck design (p < 0.001), favoring a fixedneck design 23 .…”
Section: Modularitymentioning
confidence: 99%